Animation cartoon media as an increase in dental health knowledge in elementary school children - Oktaviani Indo Syaputri; Eka Anggreni; Ngatemi Ngatemi; Rini Widiyastuti (Journal Center of Excellent : Health Assistive Technology, 2023)
Background: Dental and oral health education is a primary prevention measure before the occurrence of disease. One of the interesting media that combines sound and moving images in conveying information is animated cartoon media. Purpose: the research aims to analyze the effectiveness of Cartoon Animation Media on dental health knowledge in elementary school children. Methods: The type of research used in this study was a quasy experiment with a pretest and posttest design with one group design. This research was conducted at SDN Sawangan 07 Depok class IVA. The sampling technique used total sampling, which amounted to 32 students. The instruments used were dental health knowledge questionnaires and cartoon animation media. Data analysis was tested using paired sample t test. Results: The results of this study show that the mean of dental health knowledge before being educated using animated cartoon media is 8.9 and after being educated using animated cartoon media is 11.0, with the results of paired sample t-test p<0.001. Conclusion: cartoon animation media as an increase in dental health knowledge in elementary school children.